PENDISTRIBUSIAN ZAKAT PERDAGANGAN TELUR AYAM PETELUR (Studi Kasus di Desa Punjul Kecamatan Karangrejo Kabupaten Tulungagung) - Faidati, Ashima (IAIN Tulungagung, 2018)
ABSTRACTDisclose the reality of the results of research on zalcat trade law and the legal mechanism of zalcat trade on the provisions regarding the implementation of zakat trading egg laying eggs, which are then analyzed using the theories, so get a clear picture of the problem. The results of research that the authors get from the problem of Islamic law on the implementation of zakat egg trading laying hens in the Village Punjul Karangrejo District Tulungagung is the implementation of zakat that is less in accordance with the provisions of Islamic law of zakat issued by egg vendors laying eggs in the Village Punjul has a diversity of forms, they do not understand how the calculation of his wealth is then issued zalcat 2.5% when it reaches nisab and haul and to whom should be distributed (mustahik) that also without involving amil or other zakat body (institution). Spent his zakat on an average with bentes eggs (term brown eggs broken or broken skin) and rarely using money. From the results of the research is expected to the egg layers egg traders in Punjul Village in particular to be more aware of the obligation of zakat that must be issued with 2.5% percentage per year and more understanding about the provisions relating to zakat trade.Keywords: Distribution, Zakat Trade, Egg, Mustahik